Type 1 innate lymphoid cell–immature neutrophil axis suppresses acute tissue inflammation - Kenshiro Matsuda; Natsuki Ide; Yan Xu; Ayana Iijima; Akira Shibuya (Nature Communications)
Abstract Immature neutrophils (imNeu) are a minor population of circulating neutrophils that migrate from the bone marrow (BM) into the circulation and inflamed tissues during infection, injury, physical stress, and cancer. However, the underlying mechanism of their mobilization from BM and its pathophysiological significance remains incompletely understood. Here, we show that interferon-gamma (IFN-γ) derived from type 1 innate lymphoid cells (ILC1) enhances the migration of imNeu, but not mature neutrophils, from the BM into inflamed liver tissue with ischemia–reperfusion injury and the blood circulation during polymicrobial sepsis in mice. Mechanistically, the scaffold protein Ahnak, which is specifically expressed in imNeu, underpins Smad7 nuclear translocation in response to IFN-γ, thus downregulating C-X-C chemokine receptor 4 expression critical for neutrophil retention in the BM. Furthermore, imNeu produce interleukin-10 to ameliorate tissue inflammation. Our findings thus reveal the ILC1–imNeu axis that protects tissues from acute inflammation due to injury or microbial infection.